The Effects of Social and Demographic Factors on High-Volume Hospital and Surgeon Care in Shoulder Arthroplasty. (12th August 2022) - Testa, Edward J.; Brodeur, Peter G.; Kim, Kang Woo; Modest, Jacob M.; Johnson, Cameron W.; Cruz, Aristides I.; Gil, Joseph A.
Abstract : Introduction: This study seeks to evaluate (1) the relationship between hospital and surgeon volumes of shoulder arthroplasty and complication rates and (2) patient demographics/socioeconomic factors that may affect access to high-volume shoulder arthroplasty care. Methods: Adults older than 40 years who underwent shoulder arthroplasty between 2011 and 2015 were identified in the New York Statewide Planning and Research Cooperative System database using International Classification of Disease 9/10 and Current Procedural Terminology codes. Medical/surgical complications were compared across surgeon and facility volumes. The effects of demographic factors were analyzed to determine the relationship between such factors and surgeon/facility volume in shoulder arthroplasty. Results: Seven thousand seven hundred eighty-five patients were included. Older, Hispanic/African American, socially deprived, nonprivately insured patients were more likely to be treated by low-volume facilities. Low-volume facilities had higher rates of readmission, urinary tract infection, renal failure, pneumonia, and cellulitis than high-volume facilities. Low-volume surgeons had patients with longer hospital lengths of stay. Discussion: Important differences in patient socioeconomic factors exist in access to high-volume surgical care in shoulder arthroplasty, with older, minority, and underinsured patients markedly more likely to receive care by low-volume surgeons and facilities. This may highlight an area of potential focus to improve access to high-volume care.